Physical capabilities in football players in the under-19 category - Reis, Andrea Dias [UNESP]; Lima, Francileia Andrade; Alvares, Poliane Dutra; Silva, Antonio Gilson de Souza; Diniz, Renata Rodrigues (Inst Brasileiro Pesquisa & Ensino Fisiologia Exercicio-ibpefex, 2022)
Introduction: The analysis of physical capabilities makes it possible to identify which parameters need to be improved with physical training, as well as providing a basis for performance and broad comparison between athletes. Objective: To analyse the physical abilities of U-19 football athletes. Materials and Methods. Eleven football athletes participated in this study, with an approximate age of 17 years and a height of 1.75m. The physical abilities evaluated were: aerobic endurance (Cooper test), agility (square test), flexibility (sit and reach test), abdominal strength and endurance (abdominal test), Lower limb strength (Horizontal jump) and speed (50m run). The Shapiro Wilk test was used to verify the normality of the data and the Pearson test to verify the relationship between aerobic endurance and physical capacity variables using the Stata 14.0 software, with alpha= 5%. Results. The athletes had 2460 +/- 148.73m for the Cooper test, 5.28 +/- 0.48s for the Square test, 36 +/- 6.29cm for the Sit and reach test, 40.27 +/- 3.85 rep/min for the test of Abdominal, 281.82 +/- 28.65cm in the horizontal jump and 4.22 +/- 0.13s in the 50m run. Aerobic endurance had a slight correlation with flexibility and agility. Conclusion. Under-19 football athletes demonstrated below-average physical capacities for flexibility, yet average rating for aerobic endurance, abdominal strength and endurance, as well as above-average for agility, lower limb strength and speed. Furthermore, aerobic endurance may be related to flexibility and agility in this category.
Keywords: Athletes; Football; Physical exercise